Shortcutting the diagnostic odyssey: the multidisciplinary Program for Undiagnosed Rare Diseases in adults (UD-PrOZA) - Nika Schuermans; Dimitri Hemelsoet; Wim Terryn; Sanne Steyaert; Rudy Van Coster; Paul J. Coucke; Wouter Steyaert; Bert Callewaert; Elke Bogaert; Patrick Verloo; Arnaud V. Vanlander; Elke Debackere; et al. (Orphanet Journal of Rare Diseases, 2022)
Abstract Background In order to facilitate the diagnostic process for adult patients suffering from a rare disease, the Undiagnosed Disease Program (UD-PrOZA) was founded in 2015 at the Ghent University Hospital in Belgium. In this study we report the five-year results of our multidisciplinary approach in rare disease diagnostics. Methods Patients referred by a healthcare provider, in which an underlying rare disease is likely, qualify for a UD-PrOZA evaluation. UD-PrOZA uses a multidisciplinary clinical approach combined with state-of-the-art genomic technologies in close collaboration with research facilities to diagnose patients. Results Between 2015 and 2020, 692 patients (94% adults) were referred of which 329 (48%) were accepted for evaluation. In 18% (60 of 329) of the cases a definite diagnosis was made. 88% (53 of 60) of the established diagnoses had a genetic origin. 65% (39 of 60) of the genetic diagnoses were made through whole exome sequencing (WES). The mean time interval between symptom-onset and diagnosis was 19 years. Key observations included novel genotype–phenotype correlations, new variants in known disease genes and the identification of three new disease genes. In 13% (7 of 53), identifying the molecular cause was associated with therapeutic recommendations and in 88% (53 of 60), gene specific genetic counseling was made possible. Actionable secondary findings were reported in 7% (12 of 177) of the patients in which WES was performed. Conclusion UD-PrOZA offers an innovative interdisciplinary platform to diagnose rare diseases in adults with previously unexplained medical problems and to facilitate translational research.